Analisis Pengaruh Pertumbuhan Ekonomi Terhadap Tingkat Kemiskinan Di Provinsi Sumatera Utara (2010-2019) - Elisabeth Nainggolan (LPPM STIE EKA PRASETYA, 2020)
ABSTRACT Purpose of this observation to find out effect of economic growth on poverty levels in the period 2010-2019. The variable used is the percentage of poverty level as the dependent variable and the Gross Regional Domestic Product (GRDP) and the Open Unemployment Rate as independent variables. The data used in this study are secondary data obtained from BPS North Sumatra. The analytical method used is a multiple linear regression model or Ordinary Ordinary Least Square (OLS). In processing data, the authors use the help of Eviews 8.1 software. Based on the estimation results it is found that there is no correlation between the rate of economic growth and the poverty rate in North Sumatra and the variable Open Unemployment Rate has a positive and significant effect on poverty levels in North Sumatera Province.